2007
DOI: 10.1111/j.1439-037x.2007.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Waterlogging on Two Lucerne Varieties Grown Under Glasshouse Conditions

Abstract: Two lucerne (Medicago sativa) varieties, an anecdotally waterlogging-intolerant old New Zealand variety, Grasslands Wairau, and a reputedly waterlogging-tolerant new variety, Pioneer 54Q53, were subjected to waterlogging stress and a range of physiological and agronomic measurements performed. Waterlogging stress was characterized by measurement of soil oxygen depletion and soil carbon dioxide accumulation. Both varieties exhibited strong responses to waterlogging stress, including reduction in leaf soluble pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
19
0
2
Order By: Relevance
“…Some researchers have indicated that high carbon dioxide levels [30] [31] [32] or impaired mineral diffusion [33] in the rhizosphere are key factors influencing crop waterlogging injury. Additionally, low partial pressure of oxygen around the roots [17] [34] should be considered an important factor in the development of waterlogging injury in soybean plants.…”
Section: Analysis Of the Mechanism Underlying Field Waterlogging Tolementioning
confidence: 99%
“…Some researchers have indicated that high carbon dioxide levels [30] [31] [32] or impaired mineral diffusion [33] in the rhizosphere are key factors influencing crop waterlogging injury. Additionally, low partial pressure of oxygen around the roots [17] [34] should be considered an important factor in the development of waterlogging injury in soybean plants.…”
Section: Analysis Of the Mechanism Underlying Field Waterlogging Tolementioning
confidence: 99%
“…Condiciones de hipoxia en el medio de cultivo afectan el crecimiento, el rendimiento de la planta y la calidad del producto de los cultivos hort铆colas, debido a que se alteran procesos fisiol贸gicos y bioqu铆micos tales como el potencial h铆drico (Drew, 1997), el contenido de clorofila, fotos铆ntesis y balance hormonal por exceso de etileno (Irving et al, 2007;Horchani et al, 2008bHorchani et al, , 2009). Adem谩s, se reduce la conductancia estom谩tica (Vartapetian y Jackson, 1997), se afecta la absorci贸n, el transporte de agua y nutrientes (Stiepniewski y Przywara, 1992), y es causa de muerte celular por acidificaci贸n citoplasm谩tica (Drew, 1997) y epinastia foliar (Pezeshki, 2001).…”
Section: Introductionunclassified
“…La falta de ox铆geno induce a la respiraci贸n anaer贸bica, incrementando la concentraci贸n de etanol y CO 2 en la rizosfera hasta niveles t贸xicos (Irving et al, 2007). Los da帽os a nivel de tejidos y c茅lulas incrementaron la susceptibilidad de las ra铆ces a Phytium sp.…”
Section: Introductionunclassified
“…oxygen: 0% -21%, carbon dioxide: 0.03% -21% [15]. The origin of plant watterlogging injury has been understood as their condition, "low oxygen" [16] or "high carbon dioxide" [17][18][19].…”
Section: Introductionmentioning
confidence: 99%